Comparison of Cellular immunity in Patients with Chronic Hepatitis B, Inactive Hepatitis B Surface Antigen Carriers and Spontaneously Recovered Individuals - SİLİ, ULUHAN (H G E UPDATE MEDICAL PUBLISHING S A, 2014)
Different clinical outcomes of acute HBV infection have been partially explained by individual differences in immune response. In this study We investigated interferon gamma (IFN-gamma) secretion of peripheral blood mononuclear cells (PBMC) in vitro against specific (Hepatitis B core antigen; recombinant HBcAg) and non-specific (CMV, EBV, Influenza peptide pool; CTL CFF peptide pool plus) antigens using enzyme linked immunospot (ELISPOT) assay in 7 patients with chronic hepatitis B (CHB group), 8 inactive carriers of HBV (carrier group) and 8 subjects who spontaneously recovered from acute HBV infection as detected by anti-HBs positivity (immune group). Phytohemaglutinin served as the positive test control. Response against recombinant HBcAg was 88 +/- 35, 50 +/- 110, 105 +/- 150 spot forming cell (SFC) /10(5) PBMC, in CHB, carrier and immune groups, respectively. HBeAg-specific T-cell response was slightly higher in the immune group; however, statistically there was no significant difference between the groups. Assessment of cellular immunity by IFN-gamma ELISPOT was not sufficient to explain the various outcomes of HBV infection such as resolution, chronicity and carriership.
Keywords: Chronic hepatitis B; ELISPOT assay; Interferon gamma; VIRUS-INFECTION; RESPONSES; THERAPY; NEED